Votes and Budgets
XVIII, 270 p.
Keywords: This book presents case-studies in accountable government and the management of public funds, with particular reference to the multi-party political systems of Botswana, Jamaica, Sri Lanka and Zambia under the Third Republic. Criteria for judging accountability are set out, and the role and influence of political leadership, elections, parties, parliaments, interest groups, the media and external donors are explored. Conclusions take account of the comparisons which are drawn with the experience of single-party regimes in Africa and Asia.